The effect of temperature, pressure, and grind size on Total Dissolved Solids (TDS) and extraction yield of semi-automatic espresso machines - Winarso, Rochmad; Khoeron, Slamet; Wibowo, Rianto; Darmanto, Darmanto (Jurnal Polimesin, 2024)
The number of coffee shops in Indonesia has grown from 1,083 stalls in 2016 to over 2,937 booths in 2019, representing a threefold growth. Coffee shop establishments must provide two essential kinds of equipment: espresso machines, which use pressure, and filter machines, which employ infusion. The issue lies in the exorbitant cost and immense power requirements of semi-automatic and automated espresso machines, which necessitate the use of a manual espresso machine for commercial operations. The equipment can generate satisfactory espresso but encounters several challenges; specifically, the espresso generated is characterized by inconsistency, constantly varying in quality. This might arise due to the erratic nature of the manufacturing process. The two objectives of this study are: (1) to design an economically efficient semi-automatic espresso machine capable of producing products that meet the international quality standards set by the Specialty Coffee Association (SCA standard) and (2) to investigate the impact of critical factors such as pressure, temperature, and grind size, on the consistent quality of the resulting coffee (measured by Total Dissolved Solids (TDS) and extraction yield (EXT)). The research employs the Research and Development (RD) methodology. The research findings indicate that the optimal levels of Total Dissolved Solids (TDS) and extraction yield (EXT) may be attained by using a pressure setting of 8 bars, a temperature of 90ºC, and a grind size of 3.2 on the scale. The technique for optimizing the response resulted in Total Dissolved Solids (TDS) levels of 10.03% and extraction yield (EXT) values of 19.56%. The results have been deemed acceptable based on the criteria set by the global standards of Specialty Coffee Association (SCA).